Ethnomathematics Learning Module for the Sasak Tribe with a Deep Learning Approach for Understanding Geometry - Lalu Saparwadi; Robyan Endruw Bafadal; Rahman Ihdanul Alpan; Rahman Ihdanil Alpin; Sakrim Sakrim; I Ketut Sukarma (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to develop a mathematics teaching module based on the ethnomathematics of the Sasak tribe, incorporating deep learning principles to enhance students' understanding of geometry. The research was conducted at MTs Muhammadiyah Selong with the involvement of 17 seventh-grade students. The module development followed the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The Define stage focused on gathering information, setting learning objectives, determining the topics, and identifying the target audience and content through data collection from observations and interviews. The Design stage involved selecting the module design, format, and structure. The Develop stage included the creation and editing of the module, followed by expert validation for content and media, and a pilot test to assess its functionality. The Disseminate stage included distributing the validated module to the students for further implementation. The results of the module validation from both media and content experts showed that the module was highly valid, with an average score of 82.69% for content and 82% for media design. A small-scale trial with teachers and students indicated that the module was very practical, with an average score of 84% from teachers and 81% from students. The effectiveness of the module was tested using a paired sample T-test, which revealed a significant improvement in students' geometric understanding (p < 0.05). Furthermore, the N-gain analysis showed a moderate improvement in the students' performance. This research highlights the potential of integrating deep learning principles with local ethnomathematics in creating a meaningful, contextual, and effective learning experience for students, particularly in the understanding of geometry.